Wewenang Dan Pendelegasian dalam Perspektif Al-Qur’an (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2024)
In companies or organizations, the terms authority and delegation cannot be separated from the two. Because, authority and delegation are an integral part of the management process that cannot be separated from the company or organization. So when authority and delegation cannot be implemented properly it will have an impact on the running process of the company or organization. Therefore, to avoid things that could hamper the process of running the organization, in this study the researcher wrote a research topic about authority and delegation from the perspective of the Al-Qur'an. That way we can know the ideal authority and delegation from the perspective of the Qur'an. So that we can understand and apply authority and delegation well. This research also explains the three principles of delegation of authority from the perspective of the Qur'an, namely: gradualness, unity of command, and full authority. In this article, five characteristics are also written that must at least be possessed by people who give and receive authority, namely: trustworthy, professional, fair, honest and responsible.